Tissue Responses to Stent Grafts with Endo-Exo-Skeleton for Saccular Abdominal Aortic Aneurysms in a Canine Model - Kim, Young Il (The Korean Society of Radiology, 2014)
OBJECTIVE: We evaluated the effect of close contact between the stent and the graft on the induction of endothelial covering on the stent graft placed over an aneurysm. MATERIALS AND METHODS: Saccular abdominal aortic aneurysms were made with Dacron patch in eight dogs. The stent graft consisted of an inner stent, a expanded polytetrafluoroethylene graft, and an outer stent. After sacrificing the animals, the aortas with an embedded stent graft were excised. The aortas were inspected grossly and evaluated microscopically. RESULTS: The animals were sacrificed at two (n = 3), six (n = 3), and eight months (n = 2) after endovascular repair. In two dogs, the aortic lumen was occluded at two months after the placement. On gross inspection of specimens from the other six dogs with a patent aortic lumen, stent grafts placed over the normal aortic wall were covered by glossy white neointima, whereas, stent grafts placed over the aneurysmal aortic wall were covered by brownish neointima. On microscopic inspection, stent grafts placed over the normal aortic wall were covered by thin neointima (0.27 ± 0.05 mm, mean ± standard deviation) with an endothelial layer, and stent grafts placed over the aneurysmal aortic wall were covered by thick neointima (0.62 ± 0.17 mm) without any endothelial lining. Transgraft cell migration at the normal aortic wall was more active than that at the aneurysmal aortic wall. CONCLUSION: Close contact between the stent and the graft, which was achieved with stent grafts with endo-exo-skeleton, could not enhance endothelial covering on the stent graft placed over the aneurysms.